Students’ Attitudes on Translanguaging in the English Virtual Classroom: The Case of a State University - Vergara, Angelica Jean Del Pilar; Sumayo, Gideon Sindad (ELT Worldwide: Journal of English Language Teaching, 2025)
This study investigates university students’ attitudes toward translanguaging in English virtual classrooms and addresses a specific gap: despite the rapid normalization of online instruction, little is known about how tertiary learners in Philippine HEIs perceive translanguaging in fully digital English courses. Anchored on Translanguaging Theory, the study employed a descriptive-correlational design to determine students’ socio-demographic profiles, their reasons for using translanguaging, and how these socio-demographics relate to their perceptions of translanguaging. A total of 95 respondents from a state university participated through stratified random sampling. A modified and expert-validated survey questionnaire was utilized, and data were analyzed using descriptive and inferential statistics. Results revealed that students generally hold positive attitudes toward translanguaging, as indicated by an overall mean of 4.02, showing agreement that it supports clearer comprehension, more comfortable expression, and active participation in class. Moreover, Pearson correlation results revealed no significant relationships between attitudes and age (r = -0.087, p = .400), sex (r = -0.061, p = .556), year level (r = -0.134, p = .195), and L1 (r = -0.054, p = .601). These results suggest that students’ acceptance of translanguaging transcends socio-demographic boundaries and may be influenced more by their shared virtual learning experiences. The study concludes that translanguaging is a widely accepted and pedagogically sound approach that enhances comprehension and classroom interaction in online English instruction. It is recommended that educators incorporate translanguaging strategies to foster engagement, clarity, and inclusive participation in virtual settings.